Prevalence and factors associated to body self-perception in students from the Brazilian Northeast region - Pedraza, Dixis Figueroa (2018)
The objective was to assess body self-perception in students from the public education network of Campina Grande and to examine the association with sex, age and nutritional state. We conducted a cross-sectional study with 1.081 childrenfive to ten years old. Children were weighedand measured following standardized procedures. We obtained the nutritional state through BMI/A. To assess the body perception, we used the Children'sBody Image Scale. The overweight prevalence was 75.9%. Overweight and obese children had higher percentages of body dissatisfaction. Within obese children, 73.7% perceive themselves slimmer. The 94.7% of overweight, 98% of obese and 41.8% eutrophic children wished to be thinner, while 83.3% of malnourished children wishedto be fatter. The most distortedbody image was seen in older children and among boys. Sex, age and nutritional status can influence body perception.